PENGARUH DUKUNGAN SOSIAL DAN SELF-ESTEEM DENGAN PSYCHOLOGICAL WELL-BEING PADA KARYAWAN - Arabela Agatha Tjatura; Kurniawan, Jimmy Ellya (ITB AAS Indonesia Surakarta, 2025)
The high rates of psychological issues such as stress and depression among workers are a major concern, often rooted in low levels of psychological well-being. This study aimed to determine the influence of social support and self-esteem on the psychological well-being of employees. This research used a quantitative method with convenience sampling, and data were collected through distributed questionnaires, yielding 202 respondents who had worked for at least one year. The results showed that self-esteem had a significant positive influence on psychological well-being (p < 0.001). However, social support did not show a significant influence on psychological well-being. Nevertheless, both variables showed a significant influence on psychological well-being (p < 0.001, R² = 0.551). These results highlight the crucial role of self-esteem in enhancing employee psychological well-being, while the impact of social support in this specific context warrants further investigation.